1985
DOI: 10.2307/1590657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Kinetic-Based Enzyme-Linked Immunosorbent Assay (KELISA) and Virus-Neutralization Test for Infectious Bursal Disease Virus. I. Quantitation of Antibody in White Leghorn Hens

Abstract: The kinetics of the enzyme-substrate reaction served to evaluate a single-serum-dilution indirect enzyme-linked immunosorbent assay (ELISA) for quantitating antibody in white leghorn hens inoculated with infectious bursal disease virus (IBDV) vaccines. The antibody profiles of primary and secondary responses induced by two IBDV immunization regimens were compared using a kinetic-based ELISA (KELISA) and the virus-neutralization (VN) test. KELISA was standardized with an IBDV-infected VERO cell suspension. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The findings of this study demonstrated that a high level of mAb during primary immunization interfered with the take of IBDV vaccines. Similar finding was observed previously by Solano et al [15]. In their study, when high mAb (ELISA titer 16,384 on day 1) bearing chickens were vaccinated at 1 or 15 days of age with an intermediate live IBDV vaccine (Bursine-2), no detectable immediate primary antibody response was observed in chickens.…”
Section: Resultssupporting
confidence: 91%
“…The findings of this study demonstrated that a high level of mAb during primary immunization interfered with the take of IBDV vaccines. Similar finding was observed previously by Solano et al [15]. In their study, when high mAb (ELISA titer 16,384 on day 1) bearing chickens were vaccinated at 1 or 15 days of age with an intermediate live IBDV vaccine (Bursine-2), no detectable immediate primary antibody response was observed in chickens.…”
Section: Resultssupporting
confidence: 91%
“…Sera collected from the chickens immediately prier to, and 21 days after, challenge were tested for IBDV antibodies by an ELISA [31] using the PBG 98 IBDV strain grown in Vero cells as the antigen and a rabbit anti-chicken IgG phosphatase conjugate (Zymed) diluted 1:4000 to detect bound antibody. Sera were also tested for FPV antibodies by ELISA [23].…”
Section: Serologymentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA) is commonly used as a rapid and sensitive test for detection of IBDV antigen or antibody against IBDV (Marquardt et al, 1980;Howie andThorson, 1981 andSolano et al, 1985). ELISA is now being used for sero-profiling of chicken flocks and examination of the efficiency of vaccines (Solano et al, 1986). Studies of the molecular epidemiology of IBDV are important, and the DAS-ELISA could be an alternative technique for screening a large number of samples before testing (Tham et al, 1995).…”
Section: Introductionmentioning
confidence: 99%